Explorative studies of an innovative superconducting gantry. Issue 1 (1st January 2023) - Pullia, M G; Benedetto, E; Dassa, L; De Matteis, E; Donetti, M; Felcini, E; Frisella, G; Karppinen, M; Kurfürst, C; Mariotto, S; Mereghetti, A; Mirandola, A; et al.
Abstract: The Heavy Ion Therapy Research Integration plus (HITRIplus) is an European project that aims to integrate and propel research and technologies related to cancer treatment with heavy ion beams. Among the ambitious goals of the project, a specific work package includes the design of a gantry for carbon ions, based on superconducting magnets. The first milestone to achieve is the choice of the fundamental gantry parameters, namely the beam optics layout, the superconducting magnet technology, and the main user requirements. Starting from a reference 3 T design, the collaboration widely explored dozens of possible gantry configurations at 4 T, aiming to find the best compromise in terms of footprint, capital cost, and required R&D. We present here a summary of these configurations, underlying the initial correlation between the beam optics, the mechanics and the main superconducting dipoles design: the bending field (up to 4 T), combined function features (integrated quadrupoles), magnet aperture (up to 90 mm), and angular length (30° – 45°). The resulting main parameters are then listed, compared, and used to drive the choice of the best gantry layout to be developed in HITRI plus .